Observation of zebrafish embryonic and larval development at different doses of curcumin solution: the disparity between safe and toxic (Research, Society and Development, 2022)
The aim of the study is to perform a fast and efficient toxicity test that demonstrates the safety or toxicity levels in the embryonic development of zebrafish exposed to different doses of curcumin. Embryotoxicity tests were performed according to the OECD guideline. A standard dose of 100 mg/kg curcumin per zebrafish embryo weight was determined. A stock solution was dissolved in dimethylsulfoxide and then used to perform a serial dilution in dechlorinated water to identify safe levels of curcumin concentration. The test was performed at concentrations of 0.6; 1.25; 2.50; 5; 6.25; 10; 12.5; 25; 50; 100 μM/mL, together with a control standard containing only dechlorinated water. After the start of exposure, the embryos were monitored with an optical microscope at 8, 24, 48, 72, and 96 hours post-exposure to identify possible changes and mortality. We observed that higher doses of curcumin solution influence the appearance of teratogenic characteristics such as eye malformation, retarded growth, yolk edema, crooked syrup, and short syrup. The results were also analyzed from the embryonic survival rate from the doses used, concluding that at higher concentrations, there was a significant difference in survival.